Effects of fish meal under different storage conditions on growth, serum biochemical indices and antioxidant capacity for juvenile grouper Epinephelus coioides. (14th February 2021) - Lin, Huaxing; Yang, Qihui; Wang, Anjing; Wang, Junxian; Tan, Beiping; Ray, Gyan Watson; Dong, Xiaohui; Chi, Shuyan; Liu, Hongyu; Zhang, Shuang
Abstract: This research aimed to assess effects of fish meal under different storage conditions on growth and antioxidant capacity for juvenile grouper within eight weeks. The healthy fish samples (initial body weight = 18.75 ± 0.05 g) were irregularly distributed to 0.5 m 3 barrels with 28 fish per barrel, fed with each diet in the three replicate groups. Fish meals (FMs) were stored at 4°C (experiment 1) and room temperature (30 ± 2°C, experiment 2) for 45, 90 and 135 days, and the data of VBN, HA, AV and TBA were detected. Seven iso‐nitrogenous and iso‐lipidic diets were prepared and denoted as fresh fish meal FFM (control group), 4‐FM45, 4‐FM90, 4‐FM135, RT‐FM45, RT‐FM90 and RT‐FM135, respectively. Prolonged storage time, the volatile base nitrogen, acid value, histamine and thiobarbituric acid contents of FM increased significantly ( p < .05). The growth condition and feed utilization of experimental fish were not significantly affected ( p > .05). Prolonged storage time, in experiment 1, the catalase (CAT), the superoxide dismutase (SOD) activities and the malondialdehyde (MDA) contents initially increased dramatically and then decreased ( p < .05). The reactivity of CAT mRNA in FFM group was significantly higher than that in other treatment groups ( p < .05). In experiment 2, CAT activity decreased significantly ( p < .05), whereas the MDA contents increased sharply ( p < .05). SOD activity and CAT expression in the liver initially increased and then decreased ( p < .05). The mRNA level and enzyme activity of trypsin decreased ( p < .05) in experiment 1 and 2. In summary, storage of FM (within 135 days) cannot improve the growth and feed utilization of juvenile grouper but weaken the antioxidant capacity of the liver.